Modeling of hybrid active power filter using artificial intelligence controller: hardware and software prospective - Sandhya P.; Nagaraj R. (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
The power factor is a significant concern in power systems. The significant power loss occurred due to electronic and electrical equipment damages affected by the deviation of physical characteristics, including voltage, current, and frequency parameters.The power loss and quality issues were resolved by introducing filtering techniques in electronic and electrical equipment. Many filtering techniques include passive filtering (PF), Active power filter (APF), and many hybrid approaches are already available. Most of these methods use proper compensation controlling approaches and failed to minimize the total harmonic distortion (THD), and harmonic mitigation in power systems has its best. In this article, an efficient Hybrid-APF using Artificial-Neuro Fuzzy interface system (ANFIS) for software and hardware perspective is designed. The proposed approach uses hybrid controlling strategies which include PI with artificial intelligence (ANFIS) controller, to control the power losses for H-APF. Additionally, current compensation is achieved by PQ-theory, followed by Hysteresis-Current- Controller (HCC). The hardware architecture of ANFIS with HCC is designed to improve the chip-area for real-time power applications.The present work analyzed by simulating the voltage and current waveform. The proposed-H-APF using ANFIS controller, both software and hardware approaches, is compared with other control techniques like H-APF with PI and Fuzzy logic controller by concerning THD,Reactive power, and Different Harmonics and loads improvements.